DksA involvement in transcription fidelity buffers stochastic epigenetic change - Satory, Dominik (Nucleic Acids Res, 2015)
DksA is an auxiliary transcription factor that interacts with RNA polymerase and influences gene expression. Depending on the promoter, DksA can be a positive or negative regulator of transcription initiation. Moreover, DksA has a substantial effect on transcription elongation where it prevents the collision of transcription and replication machineries, plays a key role in maintaining transcription elongation when translation and transcription are uncoupled and has been shown to be involved in transcription fidelity. Here, we assessed the role of DksA in transcription fidelity by monitoring stochastic epigenetic switching in the lac operon (with and without an error-prone transcription slippage sequence), partial phenotypic suppression of a lacZ nonsense allele, as well as monitoring the number of lacI mRNA transcripts produced in the presence and absence of DksA via an operon fusion and single molecule fluorescent in situ hybridization studies. We present data showing that DksA acts to maintain transcription fidelity in vivo and the role of DksA seems to be distinct from that of the GreA and GreB transcription fidelity factors.